The Influence of polycyclic aromatic hydrocarbons exposure on the gut microbiome composition and inflammatory responses - Song Hee Jeong; Jaejoon Jung; Young-Jun Park; Sang Jun Lee; Seon-Jin Lee (Ecotoxicology and Environmental Safety)
Particulate matter (PM) is recognized as a contributor to various gastrointestinal diseases, including inflammatory bowel disease. However, the specific impact of polycyclic aromatic hydrocarbons (PAHs), a major component of PM, on microbial community dynamics and immune regulation remains unexplored. In this study, we investigated the effects of PAHs on the inflammatory response of mouse intestinal tissues and microbiota composition using PAHs extracted from PM10 (PM10_PAHs). With increasing duration of exposure to PM10_PAHs, damage to the colonic mucosa and lung tissues was aggravated and the secretion of inflammatory cytokines increased. The composition of the gut microbiota was also significantly altered, with a decrease in Firmicutes and an increase in Bacteroidetes at the phylum level, along with an increase in Lactobacillus, Clostridium, and Romboutsia at the genus level. Notably, despite the cessation of PM10_PAHs administration and the recovery of gut microbial diversity, the microbiota composition and inflammatory cytokine levels did not return to pre-exposure conditions. These results suggest that exposure to PM can have lasting adverse health effects, such as inflammation induced by its main component, PAHs.